PENGGUNAAN ANTIBIOTIK OLEH MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS TANJUNGPURA (THE USED OF ANTIBIOTIK AT MEDICAL FACULTY OF TANJUNGPURA UNIVERSITY) - Herlina, Tutun; Untari, Eka Kartika; Desnita, Rise (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2019)
The irrational use of antibiotics, either through prescriptionor non-prescription for sel-medication is one of main problems in the health sector through out the world. The role of health worker are the appropriate information source for antibiotic treatment. Method. The research used descriptive observational design, conducted at Medical Faculty of Tanjungpura University. The research subject were student of year 2015 in the faculty. The tool used was a questionnarie, with 32 questions. Result. The knowledge about antibiotics among student of medical faculty is categorized into a good-level (62%), quite-level (15%), and less (23%). Conclusion. From the results of this research was found that there were medical student who had less-level of knowledge about antibiotics and still using antibiotic for self-medication even though the use of antibiotics should be based on a prescription.